The Role of EFL Teachers' Self-Disclosure as Predictors of Student's Willingness to Communicate and Their Engagement - Liu, Xingpei; Zhu, Linhan (Frontiers in Psychology, 2021)
This study aims to delve into the role of teachers’ self-disclosure on developing students’ willingness to communicate (WTC) and students’ engagement. First of all, a definition of willingness to communicate is proposed, then the concept of teachers’ disclosure is explained. Moreover, the definition of engagement and its facilitators are mentioned. The interpersonal relationship between students and teachers with regard to some examples is discussed then. Finally, the significant effect of what has been disclosed by the teachers in both students’ willingness to communicate and engagement is discussed. Some limitations in this line of study and pedagogical implications are proposed for avid researchers.